Effects of growth promoting implants gains of nursing calves - Corah, L.; Kimple, K.; McKee, M.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Both steer and heifer calves gain significantly (P<.05) faster on summer pasture with growth-promoting implants than calves not implanted. Ralgro, Synovex-S, and Synovex-H were tested, with no significant advantage for one Implant type.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Growth; Implants; Gain